2021
DOI: 10.1002/jcpy.1240
|View full text |Cite
|
Sign up to set email alerts
|

Relational Spending in Funerals: Caring for Others Loved and Lost

Abstract: Funeral rituals perform important social functions for families and communities, but little is known about the motives of people planning funerals. Using mixed methods, we examine funeral planning as end‐of‐life relational spending. We identify how relational motives drive and manifest in funeral planning, even when the primary recipient of goods and services is dead. Qualitative interviews with consumers who had planned pre‐COVID funerals (N = 15) reveal a caring orientation drives funeral decision‐making for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…An example of qualitative research that was deliberately designed to make a substantive contribution can be found in Whitley et al (2021). This mixed‐methods paper developed theory relevant to the phenomenon of relational spending in the context of funerals; it relies on the analysis of depth interviews with those who have recently planned funerals to illuminate the “caring orientation” that informs consumer decision making specific to this context.…”
Section: Why Use Qualitative Approaches To Advance Consumer Psychology?mentioning
confidence: 99%
“…An example of qualitative research that was deliberately designed to make a substantive contribution can be found in Whitley et al (2021). This mixed‐methods paper developed theory relevant to the phenomenon of relational spending in the context of funerals; it relies on the analysis of depth interviews with those who have recently planned funerals to illuminate the “caring orientation” that informs consumer decision making specific to this context.…”
Section: Why Use Qualitative Approaches To Advance Consumer Psychology?mentioning
confidence: 99%
“…Collaborations among diverse scholars who are invested in exploring similar phenomena—yet have traditionally been separated by paradigms, method orientations, target journals, and scholarly networks—may advance novel insights into resource scarcity in all its forms. As seen within exemplars of multi‐method work (e.g., Bone et al, 2014; Whitley et al, 2021), diverse collaborations can offer insights about important, but under‐investigated restrictions on resource access to generate causal inferences for cross‐comparison (Table 3, Access). Furthermore, as seen within exemplars of work at the intersection of scarcity and poverty (e.g., Amir et al, 2018; Griskevicius et al, 2013; Jacob et al, 2022; Mullainathan & Shafir, 2013), diverse populations can offer insights about the converging effects of scarcity, such as caloric (vs. money or time) scarcity and attention to trade‐offs (Shah et al, 2015) or shorter‐ versus longer‐term scarcity and cognitive function (Mani et al, 2013).…”
Section: Synthesizing Resource Scarcity and Poverty: Implications For...mentioning
confidence: 99%
“…Businesses need to recognise the resource implications of life events on families. While death is negative and entails mourning (Whitley et al, 2021), a wedding is positive and celebratory. Across differences in the valence, cause or frequency of life events, consumption enables a form of control (Pavia & Mason, 2004) for consumers.…”
Section: Tailoring Marketing Activities To Life Eventsmentioning
confidence: 99%